Differing patterns of plant spinescence affect blue duiker (Bovidae: Philantomba monticola) browsing behavior and intake rates. Issue 23 (25th October 2018) - Musariri, Tongai; Pegg, Nicola; Muvengwi, Justice; Muzama, Faith
Abstract: The ways in which spines and thorns on plants affect browsing behavior and instantaneous intake rate (IIR) have been investigated for several medium and large ungulates, with most authors concluding that spines either affect the ability to obtain a full bite, or prevent the removal of twig material. We investigated how a very small ruminant, the blue duiker ( Philantomba monticola ; mass 5 kg), altered its feeding strategy when confronted with intact or despined branches of three species of woody plant that differed in leaf and spine size, density, and arrangement, viz. Dichrostachys cinerea africana, Vachellia (Acacia) karroo and Ziziphus mucronata . Increasing spine length and density reduced IIR (g/min), while bite size was directly related to leaf area. Bite rate and the lag time to taking the first bite did not differ among treatments. In all treatments, blue duikers cropped leaves in preference to pruning shoots. High spine density forced duikers to crop leaves at the ends of branches where spines were softer. At low spine density and on despined treatments, leaves midway along branches were preferred. Single bites (using incisors) were used preferentially in the presence of spines, with a shift to cheek bites on despined branches. We conclude that, as found with larger browsers, spines coupled with small leaf size provide the best defense against defoliation. Abstract : Through controlled, repeated measures experiments on habituated animals, we investigated how differing plant leaf and spine size and arrangement affected bite rate, bite size, time taken to take a first bite, instantaneous intake rate (IIR), and bite type used by a small antelope, the blue duiker ( Philantomba monticola ). Longer, closely spaced spines affected time to first bite, the type of bite used (cheek teeth or incisors), and IIR, while leaf size affected bite rate and bite size. We conclude that a combination of small leaves and dense spines limits plant tissue loss to blue duikers.